Agreement between the BRAC University and WOHA Design Pte Ltd. (2012) - BRAC University; WOHA designs Pte Ltd. (BRAC University and WOHA design Pte Ltd., 2013)
This Design agreement is made on this the 30th day of May, Two thousand and twelve of the christian era between the BRAC University, a private university incorporated under the laws of Bangladesh having its office at 66 Mohakhali, Dhaka-1212, represented by Its Vice Chancellor hereinafter referred to as the "Client" and WOHA Designs Pte Ltd., a design architect firm being a company incorporated under the laws of Singapore having its office at 29 Hong Kong Street Singapore 059668 and represented by Wong Mun Summ, hereinafter referred to as the " Design Architect" Individually referred to as "the Party " and collectively referred to as "the Parties".